Navigating Climate Change: Alberta’s Carbon Program for Sustainable Agriculture - Hanan Ishaque; Joshua Bourassa; Guillaume Lhermie (The School of Public Policy Publications)
In order to feed a growing world population, Alberta must continue supporting the province’s agricultural industry while also taking substantial steps to reduce the industry’s methane and nitrous oxide emissions to meet Canada’s climate commitments. Balancing these goals presents challenges, as implementing emission reduction measures may incur costs for producers or necessitate changes in food production practices, potentially impacting industry growth in the short term.